Impact of Transformational and Transactional Leadership on Knowledge Sharing: The Moderating Role of Collectivistic Culture Orientation - Suhana, Suhana; Fuad Mas’ud, Suharnomo Suharnomo,; Udin, Udin (Opción, 2019)
This study aims to examine the impact of transformational and transactional leadership on knowledge sharing. Two hundred and ten postgraduate students become the respondents of the study. Data are analyzed using multiple regression with SPSS software. The results indicate that transformational leadership significantly affects knowledge sharing. In conclusion, in contrast to the expectation, transactional leadership does not affect knowledge sharing. Collectivistic culture orientation further did not moderate the relationship between transformational leadership and knowledge sharing.